2021
DOI: 10.1186/s43044-021-00213-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between 24-h blood pressure variability and major adverse cardiac events (MACE) in hospitalized patients with acute myocardial infarction: a retrospective cohort study

Abstract: Background Acute myocardial infarction (AMI) is major cardiovascular disease that causes high morbidity and mortality. In AMI, ischemia and necrosis affected some cardiomyocytes leading to a decrease in myocardial contractility which is followed by an acute proinflammation reaction and increased sympathetic tone. Meanwhile, high blood pressure variability (BPV) causing an increased left ventricular workload, heart rate, myocardial oxygen demand and induces proinflamations and endothelial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
3
3
1
Order By: Relevance
“…The mean BPV value found in this study was slightly lower than the value found in the study by Harefa (2021), which looked at the relationship between major adverse cardiac events (MACE) and 24-hour blood pressure variability in hospitalized patients with acute coronary syndrome: A retrospective cohort study [1] -During the seven-day observation period, MACEs occurred in 37 percent and 15 percent of patients, respectively, in the Cesare Cuspidi study [14] and Harefa study [1] [15]. The study indicate that BPV and MACE did not have a significant correlation while the first seven days of patients with ACS.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The mean BPV value found in this study was slightly lower than the value found in the study by Harefa (2021), which looked at the relationship between major adverse cardiac events (MACE) and 24-hour blood pressure variability in hospitalized patients with acute coronary syndrome: A retrospective cohort study [1] -During the seven-day observation period, MACEs occurred in 37 percent and 15 percent of patients, respectively, in the Cesare Cuspidi study [14] and Harefa study [1] [15]. The study indicate that BPV and MACE did not have a significant correlation while the first seven days of patients with ACS.…”
Section: Discussioncontrasting
confidence: 92%
“…The rate of MACE in our study was 17,56%. This result is higher than those of the 2019 Cipto Mangunkusumo National Hospital study [1] and Anastasia et al [13] observations on ACS patients , and saw that as 15,8% and 11.9%, separately had MACE.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings were consistent with the results of the present study, which demonstrated that DBP‐ARV is an important contributing factor to increased mortality risk in patients with AMI. Additionally, a previous retrospective study indicated no significant correlation between 24 h SBP and DBP SD and ARV, and the occurrence of in‐hospital MACEs in patients with AMI 25 . Similarly, the present study showed no significant correlation between the SBP‐ARV and the risk of short‐ and long‐term death in patients with AMI.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, a previous retrospective study indicated no significant correlation between 24 h SBP and DBP SD and ARV, and the occurrence of in-hospital MACEs in patients with AMI. 25 Similarly, the present study showed no significant correlation between the SBP-ARV and the risk of short-and long-term death in patients with AMI.…”
Section: Nonlinear Relationship Between Dbp-arv and Ami Mortalitysupporting
confidence: 45%